Success Rate of Zinc Oxide Eugenol in Pulpectomy of Necrotic Primary Molars: A Retrospective Study - Zahra Bahrololoomi, Shiva Zamaninejad (Mashhad University of Medical Sciences, 2015)
Introduction: Pulpectomy is a conservative treatment plan for primary necrotic teeth and Zinc Oxide Eugenol is still a good choice as root canal filling material but long term studies on poor prognosis molars are limited and almost contradictory. The purpose of this study is to evaluate the clinical and radiographical success rate of pulpectomy of necrotic primary molars using ZOE as the root canal filling material. Methods: 152 records of 76 primary molars on which two-visit pulpectomy had been performed were selected. The records with a complete and enough clinical history and high quality radiographs of before the treatment and follow up sessions were included to the study. The least follow up was 6 months and the most one was 59 months (with the mean follow up of 24 months). The treatments were noted successful if clinically had no signs and symptoms and radiographically, the size of pathologic radiolucencies of before the treatment have been reduced or at least remained without any changes. Then obtained information was analyses in SPSS 17 and by Chi- square and Log Rank tests. Results: From all 76 cases 5 teeth (6.6%) were radiographically failed that all of them were second primary molars and 2 teeth were clinically failed (2.6%) that both were second primary molars. Conclusion: Two-visit pulpectomy of primary molars with ZOE as root canal filling materials is one of the most successful treatments for necrotic teeth